The Effect Of Implementation Of Regional Financial Management Information System (SIMDA) On Quality Of Regional Financial Statements Of Kabupaten Majene: The Effect Of Implementation Of Regional Financial Management Information System (SIMDA) On Quality Of Regional Financial Statements Of Kabupaten Majene - Wulan Ayuandiani; Junaedi Junaedi (Institute of Computer Science (IOCS), 2019)
The purpose of this study was to determine the effect ofimplementation of the Regional Financial Management Information System (SIMDA) on the quality of the financial statements in Kabupaten Majene. This research use saturation sampling who all population as sample are 58 Civil Servants (PNS) who work in Regional Office of Finance and Assets (BKAD)of KabupatenMajene. The research method uses quantitative research methods with simple linear regression data analysis techniques that are calculated manually as well as data collection techniques by means of documentation and distributing questionnaires to all Civil Servants (PNS) who work in the Financial Board and Regional Assets of Kabupaten Majene. From the results of simple linear regression calculations, the results of study indicate a correlation or relationship between the implementation of SIMDA and the quality of the financial statements in the Kabupaten Majene, where the correlation value shows a very strong relationship. Then from the results of the calculation of the statistical t test ,known t count is greater than t table, which means that the implementation of the regional financial management information system has a significant effect on the quality of the financial statements of the KabupatenMajene, so that H1 is accepted and H0 is rejected..